Live Biotherapeutic Products and Probiotics for the Skin. Issue 12 (24th October 2021) - Vargason, Ava M.; Anselmo, Aaron C.
Abstract : The skin microbiome is essential for the proper barrier functions of the skin, preventing the invasion of pathogens and regulating immune responses. When disrupted, recurrent conditions including atopic dermatitis, acne, or chronic wounds can result. Live biotherapeutic products (LBPs), an emerging class of therapeutics based on live bacteria, are promising for treating these challenging conditions. Several topical LBPs have entered clinical trials for the skin and are quickly reporting positive data from early trials. Herein, a selection of these clinical trials are analyzed to highlight the potential of topical LBPs and provide insights into their identification and development. In addition, the outstanding challenges that need to be addressed for the full translation of these LBPs into clinical therapeutics are commented. In doing so, an overview of the existing formulation landscape for microbial‐based topical products, including direct‐to‐consumer probiotics, is provided. Once the outstanding formulation and delivery challenges are addressed for LBPs and the first topical LBPs reach the market, they will be a promising modality that provides novel therapeutic mechanisms for addressing previously difficult‐to‐treat conditions. Abstract : Recent clinical trials have demonstrated the potential of live bacteria for treating microbiota‐related diseases on the skin. This perspective analyzes these trials to provide insights related to strain selection, colonization, and formulation of live biotherapeutics on the skin. Additionally, challenges and opportunities associated with the manufacturing and patient use of both probiotics and live biotherapeutics are discussed.